2021
DOI: 10.1021/acs.analchem.1c03011
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglutamate Aminopeptidase I Promotes Hepatocellular Carcinoma via IL-6/STAT3 Activation as Revealed by a Specific Biosensor

Abstract: As a global health challenge, hepatocellular carcinoma (HCC) is strongly associated with chronic inflammation. Targeting inflammation, particularly inflammatory factors, is regarded as an important strategy for HCC diagnosis and treatment. Pyroglutamic aminopeptidase I (PGP-I), a common exopeptidase, was recently identified as a novel inflammatory cytokine in cells. However, whether PGP-I is involved in HCC development and can be regarded as a biomarker remains unclear. To address this issue, endogenous PGP-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Furthermore, the fluorescent intensity of RNP increased with NTR dose and exhibited a linear correlation between 0 and 10 μg/mL (Figure b and Figure S8). The LOD was calculated to be as low as 2.2 ng/mL by using the 3σ method. Of note, the chemical basis of the sensing mechanism for RNP was validated by ESI-MS measurement (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the fluorescent intensity of RNP increased with NTR dose and exhibited a linear correlation between 0 and 10 μg/mL (Figure b and Figure S8). The LOD was calculated to be as low as 2.2 ng/mL by using the 3σ method. Of note, the chemical basis of the sensing mechanism for RNP was validated by ESI-MS measurement (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the probe (10 μM) was measured by a similar assay in the presence of various concentrations of NTR (0–10 μg/mL). The limit of detection (LOD) was calculated according to the reported general formula. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44] IL-6/ STAT3 also affects the progression of HCC. 45 Therefore, we hypothesized that IL-6 regulates the expression of MMP2 and MMP9 through upregulating the expression of IL-6R through the JAK2/STAT3 signalling pathway to affect the invasion and migration of HCC. Similarly, in this study, we found that the high expression of IL-6R promotes the proliferation and migration of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…HCC cells have a strong ability to transform normal hepatic stellate cells into cancer‐associated fibroblasts, and these activated fibroblasts promoted cancer progression by secreting angiogenic cytokines (MMP2, MMP9) 42–44 . IL‐6/STAT3 also affects the progression of HCC 45 . Therefore, we hypothesized that IL‐6 regulates the expression of MMP2 and MMP9 through upregulating the expression of IL‐6R through the JAK2/STAT3 signalling pathway to affect the invasion and migration of HCC.…”
Section: Discussionmentioning
confidence: 99%